Mongolčuud, Nėn ėrtnėės XII zuuny ėhėn Talyn nüüdėlčdijn ulamžlal - Ėrdėnėbat, Ulambajaryn; Ėnhbat, Roozongijn (MONSUDAR hėvlėlijn gazar, 2018)
Pictorial history of the Mongols and Mongolia, from antiquity to the beginning of the 12th century